Evaluating lowland coffee genotypes against leaf rust and wilt diseases in southwestern Ethiopia - Negesa, Hailu; Gidisa, Gabisa; Wubshet, Zenebe; Alemayehu, Desalegn; Belachew, Kifle; Merga, Wakuma; Beksisa, Lemi; Merga, Dawit; Zakir, Mohammedsani (Frontiers in Plant Science, 2025)
IntroductionCoffee is one of the most economically essential agricultural commodities worldwide and in Ethiopia in particular. Despite its importance, it is constrained by different factors. Among these, coffee leaf rust, caused by Hemileia vastatrix, and wilt diseases, caused by Gibberella xylarioides, are major limiting factors of coffee production. However, Ethiopia has not yet reported a commercialized resistant variety for both of these diseases. Therefore, the present study was conducted to evaluate lowland coffee genotypes against coffee leaf rust and wilt diseases under field and greenhouse conditions, respectively.MethodsA field experiment was conducted across four locations (Agaro, Teppi, Bebeka, and Gelesha) from 2021 to 2023. A randomized complete block design with three replications was used. The experiment for wilt disease was conducted on seedlings using seedling stem-nicking inoculation techniques.ResultsThe results revealed a significant difference among the genotypes in reaction to leaf rust and wilt diseases. Among the tested genotypes, I-1, I-2, K-1, and K-2 consistently showed a highly resistant reaction to leaf rust across locations, whereas one genotype (EB-1) indicated a susceptible reaction across all locations. The highest mean leaf rust severity was recorded on EB-1 (27.1%), while the lowest severity was recorded on genotype I-2 (0.35%). Similarly, four genotypes (I-1, I-2, K-1, and K-2) showed moderate resistance to wilt disease and indicated an extended incubation period compared to the susceptible control (Geisha).DiscussionAnalysis of genotype by environment (G×E) interaction indicated a highly significant interaction (P < 0.01). Among climate factors, relative humidity and maximum temperature showed a highly significant and positive correlation with coffee leaf rust. These resistant genotypes could be used by farmers as a component of integrated disease management in coffee leaf rust-prone areas of the country. In addition, end users must integrate these genotypes with other wilt management options. Overall, these genotypes can enhance the resilience of coffee production when combined with other management strategies for coffee leaf rust and wilt diseases across the lowland coffee production areas of Ethiopia.